2019
DOI: 10.1177/0731684419862350
|View full text |Cite
|
Sign up to set email alerts
|

Buckling surrogate-based optimization framework for hierarchical stiffened composite shells by enhanced variance reduction method

Abstract: The surrogate-based optimization of hierarchical stiffened composite shells against buckling is a typical multimodal and multivariables optimization problem. To improve the computational efficiency and global optimizing ability of the surrogate-based optimization of hierarchical stiffened composite shells, an enhanced variance reduction method based on Latinized partially stratified sampling and multifidelity analysis methods is proposed in this paper and then integrated into the surrogate-based optimization f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Different from the conventional lattice stiffened cylinders with uniform basic ribs, the hierarchical stiffened cylinders are composed of two kinds of ribs: the primary ribs and the basic ribs. Wang's team found that the hierarchical stiffened cylinders can effectively resist localized deformation, showcasing high load‐bearing capacity and efficiency through theoretical models 11–14 . In practice, researchers have combined the hierarchical design with composite materials to construct lightweight, full‐composite hierarchical gird‐stiffened panels for anti‐blast protective doors 15–19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from the conventional lattice stiffened cylinders with uniform basic ribs, the hierarchical stiffened cylinders are composed of two kinds of ribs: the primary ribs and the basic ribs. Wang's team found that the hierarchical stiffened cylinders can effectively resist localized deformation, showcasing high load‐bearing capacity and efficiency through theoretical models 11–14 . In practice, researchers have combined the hierarchical design with composite materials to construct lightweight, full‐composite hierarchical gird‐stiffened panels for anti‐blast protective doors 15–19 .…”
Section: Introductionmentioning
confidence: 99%
“…Wang's team found that the hierarchical stiffened cylinders can effectively resist localized deformation, showcasing high load-bearing capacity and efficiency through theoretical models. [11][12][13][14] In practice, researchers have combined the hierarchical design with composite materials to construct lightweight, fullcomposite hierarchical gird-stiffened panels for anti-blast protective doors. [15][16][17][18][19] With advancements in manufacturing technology, carbon fiber-reinforced polymer hierarchical isogrid stiffened cylinders 20 and hierarchical orthogrid stiffened cylinders 21 have been designed, manufactured, and tested.…”
Section: Introductionmentioning
confidence: 99%